Comparison of User Experience between Goal-directed and Experiential Users on Customer Satisfaction in Tourism Marketplace - Callista Chiara; Ni Ketut Wiwiek Agustina; Putu Gde Arie Yudhistira (Jurnal Sistem Informasi, 2022)
This research aimed to examine the effect of user experience on Pigijo’s website www.pigijo.com on Pigijo customer satisfaction by using an experimental study and comparing between two different groups of user behavior, namely goal-directed and experiential. The experiment was conducted using an accidental purposive sampling technique on 60 respondents divided into two groups based on user behavior. The data collection of this experiment used a questionnaire that had been tested for validity and reliability, then carried out various tests and analyses such as descriptive analysis, t-test, and regression tests. As a result of the research. It was found that the user experience on the www.pigijo.com website has a positive relationship and influence on Pigijo customer satisfaction, where the goal-directed group has a higher average rating (69.40%) and affects customer satisfaction more positively compared to the experiential group (65.50%).